Exploring Anti-Breast Cancer Effects of Live Pediococcus acidilactici and Its Cell-Free Supernatant Isolated from Human Breast Milk - Naa N. Adumuah; Jude T. Quarshie; Harry Danwonno; Anastasia R. Aikins; Elmer N. Ametefe (International Journal of Breast Cancer)
Current breast cancer treatment options are limited by drug resistance and adverse side effects, which calls for the need for alternatives or complementary remedies. Probiotic bacteria isolated from human breast milk have been shown to possess proapoptotic and anti-inflammatory properties against breast mastitis in breastfeeding mothers and are being studied as possible anticancer regimens. Thus, this study aimed at exploring the effect of lactic acid bacteria isolated from human breast milk on MDA-MB 231 breast cancer cells. A total of twenty-two bacteria were isolated from four human breast milk samples. The isolates were characterized and identified using biochemical tests and Sanger sequencing, respectively. For in vitro experiments, we used isolated P. acidilactici to treat MDA-MB-231 cells, and an MTT assay was used to detect proliferation. RT-qPCR and wound healing assays were performed to determine the effect of the isolated P. acidilactici on breast cancer cytokine expression and migration. Exposure of MDA-MB 231 breast cancer cells to live P. acidilactici and its cell-free supernatant (CFS) for 24 h resulted in a reduction in cancer cell viability. Also, the expression of the cytokines IL-6, IL-8, and IL-10 in the breast cancer cells increased following exposure to P. acidilactici and its CFS for 24 and 72 h. Additionally, the levels of the SLUG gene remained unchanged while the TWIST1 gene was upregulated following exposure of the cancer cells to bacteria, indicating that P. acidilactici may promote epithelial-mesenchymal transition in breast cancer. Finally, the CFS significantly inhibited cancer cell mobility. These findings serve as a foundation to further investigate the usefulness of P. acidilactici as a potential therapeutic agent in breast cancer therapy.